A bat algorithm for the redundancy allocation problem. Issue 5 (3rd May 2016) - Talafuse, T.P.; Pohl, E.A.
Abstract : This article uses a recently developed bat algorithm (BA) meta-heuristic optimization method to solve the reliability redundancy allocation problem (RAP). The RAP is a well-known NP-hard problem which has been the subject of much prior work, generally of a restricted form where each component must consist of identical components in parallel to make computations tractable. Meta-heuristic methods overcome this limitation and allow for larger instances to be solved for a more general case where different components can be placed in parallel. The BA has not yet been used in reliability design, as it was a method initially designed for continuous problems. A BA is devised and tested on a well-known suite of problems from the literature. It is shown that the BA is competitive with the best known heuristics for redundancy allocation.